'My whole body is at work': the silence of gendered body techniques in cork industry in an era of automation. Issue 11 (2nd November 2022) - Cunha, Liliana; Silva, Daniel; Macedo, Mariana; Lacomblez, Marianne
Abstract: Discourses about technological transformation tend to focus on technology, as if its introduction was neutral regarding local variabilities, and the men and women that make it effective. This paper focuses on the technical act. The body is where the technical acts are inscribed and it is through the body that they are exteriorised. The purpose of this paper is to analyse the operative modes associated with the technical acts, from a gender perspective, in the context of the technological transformation in cork industry. The analysis of the work activity performed by men (punching operators) and women (choosers) was supported by observations, collective interviews, and group sessions to validate the results. The findings show male- and female-specific body techniques; how the efficacy of the technical acts contributes to the debate about the limits of technology; and how body techniques and effects on health tend to remain in silence due to automation. Practitioner summary: The reconfiguration of the human-machine relationships hardly leaves room for the analysis of how the body techniques evolve. This paper shows how the efficacy of men and women body techniques contributes to the debate about the limits of technology, even if these uses of one's body entail health costs.